Protective Effects of Polyphenols against Ischemia/Reperfusion Injury - Cebova, Martina (Molecules, 2020)
Myocardial infarction (MI) is a leading cause of morbidity and mortality across the world. It manifests as an imbalance between blood demand and blood delivery in the myocardium, which leads to cardiac ischemia and myocardial necrosis. While it is not easy to identify the first pathogenic cause of MI, the consequences are characterized by ischemia, chronic inflammation, and tissue degeneration. A poor MI prognosis is associated with extensive cardiac remodeling. A loss of viable cardiomyocytes is replaced with fibrosis, which reduces heart contractility and heart function. Recent advances have given rise to the concept of natural polyphenols. These bioactive compounds have been studied for their pharmacological properties and have proven successful in the treatment of cardiovascular diseases. Studies have focused on their various bioactivities, such as their antioxidant and anti-inflammatory effects and free radical scavenging. In this review, we summarized the effects and benefits of polyphenols on the cardiovascular injury, particularly on the treatment of myocardial infarction in animal and human studies.